Penerapan Model Pembelajaran Active Learning dengan Menggunakan Games Roda Pintar untuk Meningkatkan Minat Belajar Materi Perkalian Pelajaran Matematika Kelas III SDIT Baitul Ilmi - Selvina Zulpa; Sakban Sakban; Wismanto Wismanto (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The Active Learning method is active learning. Most practitioners and observers refer to it as a learning by doing strategy. The approach views learning as a process of building understanding through experience and information. With this approach, learners' unique perceptions, knowledge and feelings influence the learning process. The problems in this study are (1) How is student interest in learning in the application of the Active Learning learning model using smart wheel games multiplication material of class III mathematics lessons SDIT Baitul Ilmi (2) Whether the application of the Active Learning learning model using smart wheel games can increase student interest in learning multiplication material of class III mathematics lessons SDIT Baitul Ilmi. This research includes Classroom Action Research (PTK) conducted in two cycles using quantitative analysis and qualitative analysis methods. Each cycle consists of four stages, namely design, implementation, observation, and reflection. The subjects of this study were third grade students of SDIT Baitul Ilmi, totalling 33 students. The research data was obtained using teacher and student observation sheets and student learning interest test results, then the data was analysed using the percentage formula. The results obtained are (1) teacher activity in cycle I using the Active Learning model from 87.50% to 93.75% in cycle II, (2) student activity in cycle I using the Active Learning model 54.64% to 85.17% and, (3) the results of student learning interest in Mathematics subjects cycle I using Active Learning 32.25% to 83.87% in cycle II. This shows that the results of students' confidence in Mathematics subjects using the Active Learning model show very positive results. Based on the results of this study, it can increase students' interest in learning to be more active and the teacher's ability to improve for the better.